2000
DOI: 10.1007/s005950070073
|View full text |Cite
|
Sign up to set email alerts
|

Late-Type Recurrence at the Port Site of Unexpected Gallbladder Carcinoma After a Laparoscopic Cholecystectomy: Report of a Case

Abstract: A 73-year-old woman had a laparoscopic cholecystectomy for unexpected gallbladder cancer and 9 days later underwent both a liver bed resection and lymph node dissection. Four years later, she underwent a further resection of a port site recurrence of gallbladder cancer and no other site of recurrence was observed. The seeding of cancer cells during the removal of the resected gallbladder might have caused this tumor. This case may show that the port site recurrence did not necessarily indicate an incurable sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 13 publications
1
21
0
Order By: Relevance
“…In all cases, no abdominal wall metastasis, including port-site recurrence, was seen. 20,21 . Peritoneal dissemination has been induced by the spread of tumor cells through gallbladder perforation 22 or CO2 pneumoperitoneum 23 .…”
Section: Methodsmentioning
confidence: 99%
“…In all cases, no abdominal wall metastasis, including port-site recurrence, was seen. 20,21 . Peritoneal dissemination has been induced by the spread of tumor cells through gallbladder perforation 22 or CO2 pneumoperitoneum 23 .…”
Section: Methodsmentioning
confidence: 99%
“…reported that the first clinical port‐site recurrence after laparoscopic cholecystectomy is found at a median of 6–10 months (range, 2 weeks–3.5 years) after surgery . A previously reported interval of late‐type recurrence was 4 years . Although port‐site excision is still subject to debate, recent studies have revealed that the technique is not associated with improved survival and should not be considered mandatory during definitive surgical treatment .…”
Section: Discussionmentioning
confidence: 99%
“…Although the known benefits of the minimally invasive technique are still valid, cancer cell dissemination, especially portsite tumor cell implantation, has been hotly debated; and late-type port-site recurrence have been reported in the literature. 13,14 Nevertheless, one large series that compared the incidence of abdominal wall recurrences among laparoscopic cases versus open cases versus laparoscopic cases converted to open cholecystectomy demonstrated that the incidence was not increased with laparoscopic surgery. 15 In our series, one patient with a port-site recurrence underwent laparoscopic cholecystectomy in 1994, when the specimen retrieval bag was not yet in use.…”
Section: Discussionmentioning
confidence: 99%